Investigation of pump and motor healthiness based on vibration analysis at uthm biodiesel plant - Bahrin, Rafie; Mustaffa, Norrizal (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Vibration is an unavoidable phenomenon in the operation of pump and motor. Vibration can occur due to imbalance, misalignment, wear, and looseness. The machine collapse may result in costly downtime. However, predicting and monitoring machine health and condition remains a challenge. Hence, an efficient diagnosis system is needed to predict the condition and consistent lead time of the machine. This study is to measure the vibration of several centrifugal pumps and motor available at UTHM Biodiesel Plant and monitor the centrifugal pump and motor health based on the vibration data. The centrifugal pumps are divided into 2 parts which are pump and motor where both consists inboard and outboard point. The measurement was conducted at three points which are horizontal, vertical, and axial. The recorded data was then analyzed and evaluated referring to ISO 10816-3. The results demonstrated that by carefully controlling the process parameters, it is possible to measure and analyze the vibration and monitor the pump and motor health based on the vibration data. It was essential to know the maximum frequency to avoid damage to the pump and motor. The findings of this study contribute to the industry which can help identify faults or detect warning signs of potential failures and give maintenance staff time to schedule required repairs and acquire needed parts.